The Realization of Cohesion Devices Applied in Students’ Business Letters - Ni Putu Evi Wahyu Citrawati; Gede Eka Wahyu (Yayasan Karinosseff Muda Indonesia, 2023)
The study aims to discover the students’competency in writing text particularly business letters in English. The study is tried to find out the cohesion devices used by the students’. The participants were the six semester of the Tourism and Business Institut. The number of participant were 50 students. They have got several treatment how to write business letter in English. After the treatment, the researcher collect and analyse data. Qualitative method is used in analysing data. The result shown several types of cohesion applied in students’ writing such as grammatical cohesion; pronoun, substitution, conjunction and lexical cohesion; synonimy, antonimy, and superordinate.